Capoeira : a martial art and a cultural tradition - Atwood, Jane. (New York : Rosen Pub. Group, 1999)
Traces the roots and history of the martial art which was developed by Brazilian slaves and combines dance, play, ritual, and self-defense.
Includes bibliographical references (p. 60) and index.
Keywords: Capoeira (Dance) -- Juvenile literature; Capoeira (Dance); Martial arts